TINJAUAN MAQASHID AS-SYARI’AH TERHADAP PERLINDUNGAN ANAK PANTI ASUHAN SITI AISYAH KABUPATEN MANDAILING NATAL - Dedisyah Putra; Asrul Hamid (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2020)
Among the main objectives of the marriage discourse is to obtain offspring and maintain the survival of Adam's children. Ideally, in every household, every parent is present and can match the child's growth and development. But in reality, there are children who are forced to be sent to an orphanage to be cared for and cared for and fulfilled their needs in order to avoid stranded child victims. This situation is often triggered due to children born into orphans, or orphans, or even orphans who grow up without ever seeing even the faces of both parents, or because of economic factors that make the sianak family decide to place them in care. This situation results in the many we find orphanages and social communities as an extension of the government in protecting and protecting every child abandoned by his parents who are then protected, cared for and cared for. One of them is by the Siti Aisyah Orphanage in Mandailing Natal Regency. The protection offered by Siti Aisyah Orphanage includes; safeguarded and protected by the minds of every child, guarded and guaranteed continuity of education, protected nasab from children who are abandoned by their own parents with good guidance and care, guarded the position of each treasure by managing various kinds of assistance that is fully used to meet all the needs of every child . This paper presents whether the Siti Aisyah Orphanage has carried out child protection in accordance with the review of maqasid ash-shari'ah which has five main main elements: Protection of religion (hifzun ad-din), protection of the soul (hifzun nafs), protection of reason (hifz al-'aql), protection and preservation of offspring (hifz an-nasl) and guarding and protecting property (hifz al-mal)